Active ageing – Enhancing digital literacies in elderly citizens - Loureiro, Ana (2018)
Being digital and information literate is crucial in nowadays society, although not every citizen has the necessary means and resources to achieve these skills, especially the elderly ones. Therefore it is necessary to develop ways to help them to enhance their digital and information competences. In this paper we will present an ongoing project that was designed and implemented with the goal to provide elderly citizens with the necessary skills of a networked society, contributing for an active ageing. The methods used were based on a set of hands on workshops delivered by a team of voluntary students and teacher, with the help of collaborators from a nursing home. The workshops were developed accordingly with the detected needs of a group of elderly citizens, based on the answers of an implemented questionnaire.